Technology and AI in Dentistry - Zink, Samantha (My University, 2024)
When the word “technology” is spoken, most individuals imagine their cell phones or laptops that they take everywhere. Or maybe they imagine gamers playing Call of Duty for hours on end. Technology is an important aspect of our society, and we place value upon it. The technological advancements in the medical world, particularly in dentistry, have impacted present and future generations. Although dentistry often gets overlooked in the medical world, oral health is incredibly vital for the health of an individual by preventing infections, diseases, and contributing to a better quality of life. Dentistry is ever-changing with new developments and technologies trying to continuously improve the oral health of patients. Understanding how dental technology evolved to where it is today, how the prevalence of artificial intelligence can be beneficial, and how this knowledge can be applied in an office setting is key to improving the lifestyles of dental patients in today’s society and the future.